(untitled) (Research, Society and Development, 2023)
The study aimed to verify which were the mental health impacts more affected to caregivers of children with autism and the difficulties for developing the necessary care. This is a descriptive exploratory research with a qualitative approach carried out from May to December 2021. The data collection occurred through the construction of an electronic questionnaire, being developed by the "snowball sampling" method, which allows the analysis of qualitative responses, therefore, after a previous contact with the group of participants was disclosed through emails and social networks (WhatsApp, Facebook, Instagram), in order to capture the largest number of caregivers of children with autism. We obtained the cooperation of 31 participants who were able to answer the questions. The results revealed that the vast majority of caregivers were female and that more than half of the children diagnosed with Autism Spectrum Disorder were male. It was evidenced that many of the caregivers had a stable fellowship, however, it was found that there were some difficulties in sharing obligations. It was verified that part of the research group had obstacles in providing qualified assistance and support for the children’s needs, most of the time due to the absence or little support and also due to the socioeconomic issue. In this sense, it was noticed that there was a vast overload for the responsible caregivers as well as a compromising of their mental health.